2015
DOI: 10.4317/medoral.20656
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of muscle alteration in oral submucous fibrosis-seeking new evidence

Abstract: BackgroundThe aim of the study was to assess the progression of Oral Submucous Fibrosis (OSF) by investigating the correlation between clinical mouth opening and muscle-epithelial distance in tissue sections. Characterization of changes involving muscle was ascertained.Material and Methods50 cases and 10 controls were included in this case-control study. Inter-incisal mouth opening was measured and classified according to Lai et al. as Group A (more than 35mm), Group B (30 to 35mm), Group C (20 to 30mm), Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Histological studies have shown that the muscle fibers undergoing necrosis are frequently delimited by edematous fluid and extravasated RBCs . An explanation for edema surrounding muscle fibers and subsequent MF in OSF was stumbled upon during the literature search (Fig. , violet box).…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have shown that the muscle fibers undergoing necrosis are frequently delimited by edematous fluid and extravasated RBCs . An explanation for edema surrounding muscle fibers and subsequent MF in OSF was stumbled upon during the literature search (Fig. , violet box).…”
Section: Discussionmentioning
confidence: 99%
“…Previous histopathological and electron microscopical studies confirmed muscle degeneration in OSMF patients 4,9) . Khanna and Andrade observed dense collagen fibres interspersed with muscle fibres in OSMF patients with mouth opening of 15-25 mm, along with this, severe muscle degeneration in advanced cases with mouth opening of less than 15 mm was also observed 7) .…”
Section: Discussionmentioning
confidence: 63%
“…Masticatory muscle involvement and replacement with fibrous tissue is noted in individuals with OSMF 9) . In previous studies, OSMF subjects revealed significant amount of muscular atrophy, degeneration and necrosis of muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restricted mouth open ing in OSF cases relies solely not only on subepithelial fibrosis but also on the degree of muscle destruction. There is a progressive decline observed in the muscle fibers from the epithelial surface as the advancement of OSF occurs (53). Also, features suggestive of muscle atrophy and necrosis have been demonstrated in moderate and advanced OSF cases (54).…”
Section: Discussionmentioning
confidence: 96%